1991
DOI: 10.1111/j.1365-2125.1991.tb03856.x
|View full text |Cite
|
Sign up to set email alerts
|

Differing calcium sensitivities of human cerebral and digital arteries, human metatarsal veins, and rat aorta.

Abstract: Keywords digital artery metatarsal vein basilar artery calcium nifedipine rat aorta potassium noradrenaline U46619 5-hydroxytryptamine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Secondly, rat aortic contractions evoked by 5-HT depend on Ca 2 in¯ux (Okoro & Marwood 1997b) and the current data indicate that the resulting contractions are sensitive to blockade by a series of L-type Ca 2 -channel antagonists as documented previously (Gouw et al 1989;Iwanov & Mould 1991). The current IC50 values (Table 1) are, however, different from those reported by the investigators cited above.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…Secondly, rat aortic contractions evoked by 5-HT depend on Ca 2 in¯ux (Okoro & Marwood 1997b) and the current data indicate that the resulting contractions are sensitive to blockade by a series of L-type Ca 2 -channel antagonists as documented previously (Gouw et al 1989;Iwanov & Mould 1991). The current IC50 values (Table 1) are, however, different from those reported by the investigators cited above.…”
Section: Discussionsupporting
confidence: 39%
“…The current IC50 values (Table 1) are, however, different from those reported by the investigators cited above. It should be noted that our method of assessing antagonist potency against 5-HT-induced contractions was similar to those of Gouw et al (1989) but different from those of Iwanov & Mould (1991). Further, many of these studies were undertaken on aorta derived from different rat strains, and tissue contact time with antagonist drugs was brief, often less than 20 min, compared with 45 min or more in this study.…”
Section: Discussionmentioning
confidence: 99%
“…6a and 6b), whereas higher concentrations of Cardiovascular Drug Reviews, Vol. 18 ET-1 induced a biphasic increase in [Ca 2+ ] i consisting of an initial transient phase and a subsequent sustained phase ( Fig. 6c) (16,17,38).…”
Section: Ca 2+ Entry Channels Involved In the Et-1-induced Increases mentioning
confidence: 94%
“…However, subsequent studies have shown that the agonist-induced contractions and increases in [Ca 2+ ] i are virtually resistant to or only partially sensitive to specific blockers of L-type voltage-operated Ca 2+ channels (VOCCs) such as dihydropyridines (6)(7)(8)14,18,19,28,33,35,39). Thus, it is now clear that Ca 2+ entry through ion channels other than VOCCs plays a critical role in the agonists-induced contractions and increases in [Ca 2+ ] i .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation